The Power of Silence - Ashley, Florence (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
In conversation with Hortense Gallois’ recent essay on the importance of bioethicists participating in public discourse, I suggest that speaking up is as fraught as it is important. Focusing on the anti-trans movement’s misuse of expertise, I highlight the fine line between correcting misinformation and inadvertently causing harm through ill-timed speech. Drawing on the work of Eva Feder Kittay, I suggest that knowing when to speak up and when to stay silent starts with understanding the communities we speak about and the consequences that our words can have on them.